1974
DOI: 10.2105/ajph.64.3.205
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to explaining sick-role behavior in low-income populations.

Abstract: Although adherence to medical instructions is usually essential to successful health outcomes, compliance rates (especially in low-income populations) are very inadequate, and little is known about factors influencing such sick-role behaviors. The present study examines the explanatory value of a behavioral model, derived from social psychological theory, and employing health motivations, perceptions, and attitudes of mothers as predictors of compliance with regimens prescribed for their children. poor complia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
135
1
2

Year Published

1979
1979
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(141 citation statements)
references
References 20 publications
3
135
1
2
Order By: Relevance
“…A positive correlation between knowledge of cancer genetics and use of CM has been confirmed by study [15] on cancer survivors, and a positive association between perceived risk and CM use was found in unaffected people, but not in cancer patients. It has been consistently demonstrated that risk and knowledge perception are important factors motivating people to seek information or professional help for health related issues [16,17], supporting the Health Belief Model [18] which suggests that perceived susceptibility is a strong contributor in preventive health behaviours. H1N1 flu (swine flu) was a relatively unfamiliar infectious disease at the time the current research was conducted, thus it was intriguing to investigate people's attitudes and therapeutic choice for illnesses that they never experienced and were unfamiliar with.…”
Section: Perceived Riskmentioning
confidence: 88%
“…A positive correlation between knowledge of cancer genetics and use of CM has been confirmed by study [15] on cancer survivors, and a positive association between perceived risk and CM use was found in unaffected people, but not in cancer patients. It has been consistently demonstrated that risk and knowledge perception are important factors motivating people to seek information or professional help for health related issues [16,17], supporting the Health Belief Model [18] which suggests that perceived susceptibility is a strong contributor in preventive health behaviours. H1N1 flu (swine flu) was a relatively unfamiliar infectious disease at the time the current research was conducted, thus it was intriguing to investigate people's attitudes and therapeutic choice for illnesses that they never experienced and were unfamiliar with.…”
Section: Perceived Riskmentioning
confidence: 88%
“…In conclusion, both in times of growth and in times of recession, crime are being affecting quantitatively and structurally as Becker et al [19] put it in the economic theory of crime: potential criminals spend their time both illegal and legitimate activities, which depended on taking risks and rewards associated with each other. The legal rewards will depend on the levels of wages and illegal, in an extent, on the availability of goods for theft.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between HC and CBBE is explained by using the health belief model theory and brand value concept (e.g., Becker, Drachman & Kirscht, 1974;Dawar, 1998;Dawar & Pillutla, 2000;Kamakura & Russell, 1993;Narayana, 2009). In fact, the health belief model theory is rooted from a well established body of psychological and behavioral theory (Janz & Becker, 1984) and it is designed by Hochbaum et al in the 1950s (Glanz & Rimer, 1995;Janz & Becker, 1984;Rosenstock, 1974).…”
Section: Health Consciousness-customer Based Brand Equity: Theoreticamentioning
confidence: 99%
“…According to the health belief model theory people expect health actions to prevent illness, since they do not want to get sick and these health actions for prevent sick creates better choices, especially brand choice (e.g., Becker et al, 1974;Janz & Becker, 1984;Narayana, 2009). In other words, the health belief model theory supports the HC and brand choice and therefore, this study makes link between the HC and CBBE by using this model.…”
Section: Health Consciousness-customer Based Brand Equity: Theoreticamentioning
confidence: 99%